2016
DOI: 10.1108/jat-07-2015-0021
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of seniors towards automatic in home fall detection devices

Abstract: Purpose Senior citizen falls are one of the highest-cost factors of healthcare within this population group. Various approaches for automatic fall detection exist. However, little is known about the seniors’ acceptance of these systems. The purpose of this paper is to investigate the acceptance of automatic fall detection devices as well as the technological commitment and the health status in community-dwelling adults with a predefined risk of falling. Design/methodology/approach Seniors with a risk of fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Concerning fall detection, several studies concluded that, in order to be used, fall detection devices must not stigmatize people nor disturb their daily life [19][20][21]. Unfortunately, devices such as ad-hoc wearable devices and ambient sensors are not well accepted by elderly people because mostly of their intrusiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning fall detection, several studies concluded that, in order to be used, fall detection devices must not stigmatize people nor disturb their daily life [19][20][21]. Unfortunately, devices such as ad-hoc wearable devices and ambient sensors are not well accepted by elderly people because mostly of their intrusiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Wearable sensors are divided in two main groups: ad-hoc wearable devices (e.g., SHIMMER sensor nodes), and smartphones (e.g., Android). For what concerns fall detection, several studies concluded that, in order to be used, fall detection devices must not stigmatize people nor disturb their daily life [14,15,16]. Unfortunately, devices such as ad-hoc wearable devices and ambient sensors are not well accepted by elderly people because mostly of their intrusiveness.…”
Section: Introductionmentioning
confidence: 99%